Health and environmental aspect of wastewater reuse - Pescod M.B. (Reuse of low quality water for irrigation, 1989)
Wastewater irrigation is being practised in many countries around the world. Treated effluent reuse has special significance for developing countries with arid and semi-arid climates and limited water resources. Land application of wastewater and sludge provides nutrients for crop growth as well as organic matter for soil conditioning and it is often the most economic means of wastewater and sludge disposal. However, land application involves health and environmental risks, because sludge may contain heavy metals and industrial organic compounds, and wastewater and sludge may contain pathogens at detrimental concentrations. In developing countries, raw sewage is rarely treated before being applied in irrigation and this direct reuse without any restrictions on the types of crops poses potential health hazards and adverse environmental impacts. However, if appropriate low-cost technology for wastewater treatment and effluent distribution in irrigation can be developed to suit conditions in developing countries and provide the necessary safeguards to health, this form of reuse will conserve valuable water resources and increase crop production.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)